Leverage, Kepemilikan Institusional, Dan Transfer Pricing, Penghindaran Pajak: Profitabilitas Sebagai Variabel Moderasi - Suyanto; Esti Sujannah (Yayasan Literasi Ilmiah Indonesia, 2021)
Purpose: This study aim to examine leverage, institutional ownership and transfer pricing, tax avoidance: profitability as moderating variablesMethod: The method in this study using purposive sampling method and obtained 40 companies with data processed 160 annual financial statements. This research technique uses multiple linear analysis and Moderated Analysis ModeratedFinding: The findings in this study that leverage has a negative effect on tax avoidance, institusional ownership has a positive effect on tax avoidance, and transfer pricing has a positive effect on tax avoidance. Profitability can weaken the negative effect of leverage on tax avoidance, profitability cannot moderate the positive effect of institutional ownership on tax avoidance, and profitability cannot significantly moderate the effect of transfer pricing on tax avoidance. Novelty: The difference between this study and previous research is that this research tries to integrate several topics regarding the variable of tax avoidance practices which are influenced by three variables including leverage, institutional ownership, and transfer pricing, using the moderating variable of profitability.